Xenogeneic collagen matrix versus connective tissue graft for the treatment of multiple gingival recessions: A systematic review and meta‐analysis - Mohammed A. AlSarhan; Reham Al Jasser; Mohammad Abdullah Tarish; Anas I. AlHuzaimi; Hamad Alzoman (Wiley, 2019)
Abstract A systematic review and meta‐analysis was performed to understand the efficacy of xenogeneic collagen matrix (CMX) compared with connective tissue graft (CTG) for the treatment of multiple adjacent gingival recessions (MAGRs). A literature search was performed for published randomized controlled trials in adult patients (≥18 years old) with Multiple Adjacent Miller class I and II gingival recessions (MAGRs). The assessments included recession depth, Recession width, complete root coverage, mean root coverage, probing depth, clinical attachment level, and keratinized tissue width. Pooled data were analyzed using fixed‐ and random‐effects models, and Forest plots were constructed. Heterogeneity within studies was calculated to assess publication bias. Four randomized controlled trials were included based on the eligibility criteria. Although the recession depth, complete root coverage, and mean root coverage were significantly lower with CMX (p = .017 and p = .001, p = .001, respectively), there was no statistically significant difference in the Recession width between CMX and CTG (p = .203). CMX showed significantly lower Probing Depth than CTG (p = .023); however, no significant difference in clinical attachment level (p = .060) and keratinized tissue width (p = .052) was observed between the groups. Owing to the heterogeneity in the included studies, firm conclusions cannot be drawn regarding the noninferiority of CMX compared with CTG. Long‐term studies are therefore needed to conclusively establish the relative efficacy of CMX in MAGR.